2016
DOI: 10.5665/sleep.6022
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Sex Differences in Insomnia Symptoms in Adolescents: A Large-Scale School-Based Study

Abstract: Chinese Clinical Trial Register, http://www.chictr.org.cn, ID: ChiCTR-TRC-12002798.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 52 publications
(78 reference statements)
5
94
3
9
Order By: Relevance
“…The excess of SC and SB in girls might suggest bidirectional interplay between both types of symptoms, under the influence of gender difference and hormonal processes. In the same direction, some authors have reported that complaints of insomnia might be influenced by pubertal developmental stages . Concerning the overlap between SC and SB, early awakening and daytime sleepiness were the sleep symptoms most related to self‐harm cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 90%
“…The excess of SC and SB in girls might suggest bidirectional interplay between both types of symptoms, under the influence of gender difference and hormonal processes. In the same direction, some authors have reported that complaints of insomnia might be influenced by pubertal developmental stages . Concerning the overlap between SC and SB, early awakening and daytime sleepiness were the sleep symptoms most related to self‐harm cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 90%
“…Age, gender, and IQ were selected as covariates given their associations with sleep and/or procedural learning (Colrain and Baker, 2011; Gomar et al, 2011; Zhang et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…found an association of female gender with high PSQI scores in a community-dwelling adults sample5. A recent school-based study with 7,507 children and adolescents showed higher prevalence of insomnia symptoms in girls than boys6, indicating that a gender difference may extend across the life course. However, Buysse and colleagues previously found no significant gender differences in PSQI among healthy young and elderly subjects7.…”
mentioning
confidence: 99%